Grief Functions as an Honest Indicator of Commitment. (May 2014) - Winegard, Bo M.; Reynolds, Tania; Baumeister, Roy F.; Winegard, Benjamin; Maner, Jon K.
Grief is a puzzling phenomenon. It is often costly and prolonged, potentially increasing mortality rates, drug abuse, withdrawal from social life, and susceptibility to illness. These costs cannot be repaid by the deceased and therefore might appear wasted. In the following article, we propose a possible solution. Using the principles of social selection theory, we argue that an important selective pressure behind the human grief response was the social decisions of other humans. We combine this with insights from signaling theory, noting that grief shares many properties with other hard-to-fake social signals. We therefore contend that grief was shaped by selective forces to function as a hard-to-fake signal of (a) a person's propensity to form strong, non-utilitarian bonds and (b) a person's current level of commitment to a group or cause. This theory explains many of the costly symptoms of grief and provides a progressive framework for future research.